Ethics, Animal Welfare, and Artificial Intelligence in Livestock: A Bibliometric Review - Taize Calvacante Santana; Cristiane Guiselini; Héliton Pandorfi; Ricardo Brauer Vigoderis; José Antônio Delfino Barbosa Filho; Rodrigo Gabriel Ferreira Soares; Maria de Fátima Araújo; Nicoly Farias Gomes; Leandro Dias de Lima; Paulo César da Silva Santos (AgriEngineering)
This study presents a bibliometric review aimed at mapping and analyzing the scientific literature related to the ethical implications of artificial intelligence (AI) in livestock farming, which is a rapidly emerging yet still underexplored field in international research. Based on the Scopus database, 151 documents published between 2015 and 2025 were identified and analyzed using the VOSviewer version 1.6.20 and Biblioshiny for Bibliometrix (RStudio version 2023.12.1) tools. The results show a significant increase in publications from 2021 onwards, reflecting the growing maturity of discussions around the integration of digital technologies in the agricultural sector. Keyword co-occurrence and bibliographic coupling analyses revealed the formation of four main thematic clusters, covering technical applications in precision livestock farming as well as reflections on governance, animal welfare, and algorithmic justice. The most influential authors, high-impact journals, and leading countries in the field were also identified. As a key contribution, this study highlights the lack of robust ethical guidelines and proposes future research directions for the development of regulatory frameworks, codes of conduct, and interdisciplinary approaches. The findings underscore the importance of aligning technological innovation with ethical responsibility and social inclusion in the transition to digital livestock farming.